Direct Observation of Enhanced Raman Scattering on Nano-Sized ZrO2 Substrate: Charge-Transfer Contribution - Ji, Peng; Wang, Zhe; Shang, Xiaohong; Zhang, Yu; Liu, Yikuan; Mao, Zhu; Shi, Xiumin (Frontiers in Chemistry, 2019)
Direct observation of the surface-enhanced Raman scattering (SERS) of molecules adsorbed on nano-sized zirconia (ZrO2) substrates was first reported without the need for the addition of metal particles. It was found that ZrO2 nanoparticles can exhibit unprecedented Raman signal enhancements on the order of 103 for the probe molecule 4-mercaptobenzoic acid (4-MBA). The dramatic effect of the calcination temperature on the ZrO2 nanoparticles was also investigated. The ZrO2 nanoparticles with the particle diameter of 10.5 nm, which were prepared by calcination at a temperature of 500°C, have the highest SERS activity. A comparison between the experimental and calculation results indicates that charge transfer (CT) effects dominate the surface enhancement. The plentiful surface state of ZrO2 active substrate that is beneficial to CT resonance occurs between molecules and ZrO2 to produce a SERS effect. The CT process depends, to a large extent, on the intrinsic properties of the modifying molecules and the surface properties of the ZrO2. This is a new SERS phenomenon for ZrO2 that will expand the application of ZrO2 to microanalysis and is beneficial for studying the basic properties of both ZrO2 and SERS.